BETWEEN DISCOURSE AND PRACTICE: ETHIC CONCEPTIONS AND CITIZENSHIP IN THE BRAZILIAN LUTHERAN CHURCH’S COMMUNITARIAN EDUCATIONAL CRISIS IN THE 80’S. - Ahlert, Alvori (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
Based on concepts of ethics and citizenship, we have carried out  an interpretative reading about the crisis mentioned in the main normative documents leading  the direction of theLuteranChurchin Brazil (IECLB) and its network of associated schools (Rede Sinodal de Educação). We have examined the minutes of Education Board of IECLB and the Evangelical Association of Education, some of the main studies and documents that record lectures sponsored by the Education Board, public manifestos and reports written by  IECLB Pastor, President of the IECLB. These interpretations allowed us to say that schools of evangelical Lutheran confession have experienced a crisis of identity, policy, direction and meaning in the 80s, bringing about an estrangement between schools and communities of maintenance, or in many cases, individual practices and centralization of power.